Direct experimental determination of the topological winding number of skyrmions in Cu2OSeO3 - S. L. Zhang (Nature Portfolio, 2017)
Experimental demonstrations of topologically nontrivial states in magnetic films currently rely on indirect comparisons of theoretical models with microscopic images. Here the authors show that resonant X-ray scattering provides direct information on the topology of magnetic textures.